The academic profession in Malaysia 2010: a proposed study - Pang, Vincent; Sirat, Morshidi; Md. Yunus, Aida Suraya; Pandian, Ambigapathy; Md. Taib, Fauziah; Shuib, Munir; Azman, Norzaini; Lie, Koo Yew; Abdul Rahman, Shukran; Bakar, Rosni; Fah, Lay Yoon; Thurasamy, Ramayah; et al. (Research Institute for Higher Education Hiroshima University, 2011)
Universities have frequently been regarded as key institutions involved in processes of social change and development. In relation to this role, Malaysian universities have realigned themselves towards goals like creating a ‘knowledge society’, an ‘achievement society’, a ‘democratic society’, a ‘global society’ or more likely, a combination of all of the above. The roles played by universities in the development period are varied, multiple and contradictory; sometimes reproductive of the status quo and sometimes transformative (Brennan & Lebeau, 2002). The main focus of a ‘traditional university’ in the Malaysian context is viewed in terms of its three primary functions: education, research and service to the community.